Effective Online Method of Teaching English - Radjabova Jayron Ikram qizi (Genius Journals, 2023)
Due to the high importance of Internet technologies, the opportunity to learn foreign languages, in particular English, in a new way, carefully opened the methods for learning English taking into account the use of Internet resources offering 4 effective foreign language teaching methods with the usage of Internet technologies. Distance learning is an integral part of modern educational model, requiring an educational institution and each teacher in particular to revise teaching methods and techniques in accordance with new standards and technologies. Remote educational technologies using the Internet are used today both for the development of individual advanced training courses for users, as well as higher education. Distance learning lessons, conferences, seminars, business games, laboratory work, workshops and other forms of training sessions conducted by means of telecommunications and other opportunities of the World Wide Web, allow teachers to increase motivation for students in the discipline and qualitatively improve learning outcomes.
Keywords: remote teaching; using digital tools; student and teacher interaction; hybrid teaching